From the Combat Medic to the Forward Surgical Team: The Madigan Model for Improving Trauma Readiness of Brigade Combat Teams Fighting the Global War on Terror - Sohn, Vance Y.; Miller, Joseph P.; Koeller, Craig A.; Gibson, Steven O.; Azarow, Kenneth S.; Myers, Jerome B.; Beekley, Alec C.; Sebesta, James A.; Christensen, Jon B.; Rush, Robert M. (The Journal of surgical research, 2007)
Medics assigned to combat units have a notable paucity of trauma experience. Our goal was to provide intense trauma refresher training for the conventional combat medic to better prepare them for combat casualty care in the War on Terror. Our Tactical Combat Casualty Care Course (TC3) consisted of the following five phases: (1) One and one-half-day didactic session; (2) Half-day simulation portion with interactive human surgical simulators for anatomical correlation of procedures and team building; (3) Half-day of case presentations and triage scenarios from Iraq/Afghanistan and associated skills stations; (4) Half-day live tissue lab where procedures were performed on live anesthetized animals in a controlled environment; and (5) One-day field phase where live anesthetized animals and surgical simulators were combined in a real-time, field-training event to simulate realistic combat injuries, evacuation problems, and mass casualty scenarios. Data collection consisted of surveys, pre- and posttests, and after-action comments. A total of 1317 personnel participated in TC3 from October 2003 through May 2005. Over the overlapping study period from December 2004 to April 2005, 327 soldiers participated in the formal five-phase course. Three hundred four (94%) students were combat medics who were preparing for combat operations in Iraq or Afghanistan. Of those completing the training, 97% indicated their confidence and ability to treat combat casualties were markedly improved. Moreover, of those 140 medics who took the course and deployed to Iraq for 1 year, 99% indicated that the principles taught in the TC3 course helped with battlefield management of injured casualties during their deployment. The hybrid training model is an effective method for training medical personnel to deal with modern battle injuries. This course increases the knowledge and confidence of combat medics deploying and fighting the Global War on Terrorism.